Epidemiology and Factors Influencing Davis Cup Retirements Over the Past Twenty Years - Martí Casals; Jordi Cortés; Daniel Llenderrozos; Miguel Crespo; Timothy E. Hewett; Lorena Martin; Ernest Baiget (International Journal of Sports Physical Therapy)
# Background